Contribution of research and education network TARENA-CAREN into monitoring of potentially hazardous objects in Tajikistan - G. Kohirova (MANAS: Journal of Engineering)
Monitoring of potentially hazardous near-Earth objects are carrying out in the Institute of Astrophysics of the Academy of Sciences of the Republic of Tajikistan. There are asteroids, comets, large sized meteoroids, space debris. Such observations are very important because some of these objects represent danger due to possible impacts with the Earth. Monitoring allows the controlling the orbits and thus the development of mitigation strategy. The observations are performing in the Gissar and Sanglokh astronomical observatories which are supplied by telescopes and connected with Internet by TARENA. The increasing of the effectiveness of monitoring provided by the TAREN-CAREN services is shown in the paper